Artificial Intelligence (AI) and Machine Learning (ML) Tools Supporting Processes - Threats, Challenges and Benefits for The Organization - Artur ZIEBA-KOZARZEWSKI (Communications of International Proceedings, 2025)
The launch of OpenAI's chatbot in the final quarter of 2022 marked as a major milestone in the development of artificial intelligence (AI). The rise of AI tools has broadened their use across a wide range of fields, potentially boosting both productivity and creativity. However, the widespread adoption of AI also presents challenges, such as maintaining quality, ensuring data integrity, and addressing security risks. Organizations must develop clear policies to maximize the benefits of AI while minimizing its associated risks. Paper proposes straightforward categorisation rules for AI powered systems. The future of industry depends on striking a balance between innovation and responsible use, ensuring that AI tools are cost-effective, efficient and secure.
Keywords: large language models; security; risks; business process; chatgpt